Retrospective Analysis of Osteoporotic Vertebral Fractures - Mustafa Can Şenoymak (Ahi Evran Medical Journal)
Osteoporotic fractures represent preventable conditions that pose significant challenges, particularly in the geriatric population, leading to considerable morbidity, mortality, and healthcare expenses. I extend my appreciation to Akar and the editorial board for their article titled 'Retrospective Analysis of Osteoporotic Vertebral Fractures' published in the third issue of Ahi Evran Medical Journal in 2023. In this letter I intend to adress particular aspects, which I believe will contribute to discussion of the article.